The Effect of Steaming and Frying Time on the Quality of Chips from Durian Seed - Loira Ambarita; Setyohadi Setyohadi; Lasma Nora Limbong (Universitas Sumatera Utara, 2013)
This research was conducted to find the effect of steaming and frying time on the quality of chpis from durian seed. The research had been performed using factorial completely randomized design with two factors, i.e the steaming time (W): (10, 15, 20 and 25 minutes), and frying time (P) : (1, 2, 3 and 4 minutes). Parameters analyzed were moisture content, fat content, yield and organoleptic values (colour,taste and flavor, and crispiness).The results showed that the steaming time had highly significant effect on moisture content, fat content, yield, colour, taste and flavor, and crispiness. Frying time also had highly significant effect on moisture content, fat content, yield, colour, taste and flavor, and crispiness. The interaction of the two factors had highly significant effect on moisture content, fat content, and yield .The 25 minutes of steaming and 4 minutes of frying gave the best quality of chips from durian seed. Keywords : Chips from durian seed, steaming time and frying time.